Development of Polish Speech Test Signal and its Comparison with International Speech Test Signal - HABASIŃSKA, Dorota; SKRODZKA, Ewa Barbara; BOGUSZ-WITCZAK, Edyta (Archives of Acoustics, 2018)
The aim of this study was to create a single-language counterpart of the International Speech Test Signal (ISTS) and to compare both with respect to their acoustical characteristics. The development procedure of the Polish Speech Test Signal (PSTS) was analogous to the one of ISTS. The main difference was that instead of multi-lingual recordings, speech recordings of five Polish speakers were used. The recordings were cut into 100–600 ms long segments and composed into one-minute long signal, obeying a set of composition rules, imposed mainly to preserve a natural, speech-like features of the signal. Analyses revealed some differences between ISTS and PSTS. The latter has about twice as high volume of voiceless fragments of speech. PSTS’s sound pressure levels in 1/3-octave bands resemble the shape of the Polish long-term average female speech spectrum, having distinctive maxima at 3–4 and 8–10 kHz which ISTS lacks. As PSTS is representative of Polish language and contains inputs from multiple speakers, it can potentially find an application as a standardized signal used during the procedure of fitting hearing aids for patients that use Polish as their main language.